Assessment of the operation status of electronic prescription at community pharmacies in Chengdu, China: a simulated patient study - Wenxin Zhou; Jing Wang; Qinmin Chen; Zhen Huang; Naitong Zhou; Ming Hu (BMC, 2023)
Abstract Background Information and technologies relevant to eHealth have developed rapidly over the past two decades. Based on this, China piloted "Internet + " pattern and some regions piloted electronic prescription services to explore telepharmacy services. Objective To describe the processes and assess the operation status of electronic prescription services mode for community pharmacies in China. Methods The simulated patient methodology was used to conduct a cross-sectional study in 317 community pharmacies from six districts in Chengdu, China in 2019. Simulated patients expressed three levels of service demands based on scenario about acute upper respiratory tract infections to evaluate the recommendation strength of electronic prescription services and telepharmacy service in community pharmacies. The descriptive statistics was completed to obtain the characteristics of the visit process, student t-test and χ2 test (P < 0.05 was considered statistically significant) were used for inferential statistical analysis to determine differences in characteristics and degree of recommendation between pharmacies. Results Three Hundred Seventeen record sheets were effectively collected. The third-party platform was recommended in 195 (61.5%) interactions. The main reason for not recommending is non-prescription dispensing of prescription drugs (27.1%). 90.3% interactions waited less than 1 min, the counseling duration was less than 5 min in all interactions, and most community pharmacies had good network conditions (81.5%). 97.4% remote physicians offered professional counseling, only 22.1% of the pharmacists provided medication advice. Conclusions The electronic prescription services mode for community pharmacies in Chengdu provides a convenient drug purchase process but remains some problems. For example, prescribing drugs without a prescription and services provided by pharmacists was poor, etc. The relevant supporting policies should be improved in future development process.